2020
DOI: 10.3390/cells9051230
|View full text |Cite
|
Sign up to set email alerts
|

Lactulose and Melibiose Inhibit α-Synuclein Aggregation and Up-Regulate Autophagy to Reduce Neuronal Vulnerability

Abstract: Parkinson’s disease (PD) is a neurodegenerative disease characterized by selective dopaminergic (DAergic) neuronal degeneration in the substantia nigra (SN) and proteinaceous α-synuclein-positive Lewy bodies and Lewy neuritis. As a chemical chaperone to promote protein stability and an autophagy inducer to clear aggregate-prone proteins, a disaccharide trehalose has been reported to alleviate neurodegeneration in PD cells and mouse models. Its trehalase-indigestible analogs, lactulose and melibiose, also demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 61 publications
(81 reference statements)
0
15
0
Order By: Relevance
“…Indole derivative NC001-8 also protects DAergic neurons derived from SH-SY5Y or iPSCs carrying PRKN mutation against MPP + and H 2 O 2 -induced neurotoxicity by up-regulating NRF2 and NQO1 [ 98 ]. By up-regulating autophagy and NRF2 pathway, disaccharides, including trehalose, lactulose and melibiose, demonstrate neuroprotective effects against α-synuclein-induced neurotoxicity [ 283 ]. Several natural compounds, such as kahweol [ 284 ], luteolin [ 285 ], ginsenoside Rb1 [ 286 ], eriodictyol [ 287 ], licochalcone A [ 288 ], genipin [ 97 ] and gastrodin [ 289 ] also demonstrate neuroprotective effects by up-regulating NRF2 pathway in different PD models.…”
Section: Potentials Of Antioxidants In Treating Parkinson’s Diseasmentioning
confidence: 99%
“…Indole derivative NC001-8 also protects DAergic neurons derived from SH-SY5Y or iPSCs carrying PRKN mutation against MPP + and H 2 O 2 -induced neurotoxicity by up-regulating NRF2 and NQO1 [ 98 ]. By up-regulating autophagy and NRF2 pathway, disaccharides, including trehalose, lactulose and melibiose, demonstrate neuroprotective effects against α-synuclein-induced neurotoxicity [ 283 ]. Several natural compounds, such as kahweol [ 284 ], luteolin [ 285 ], ginsenoside Rb1 [ 286 ], eriodictyol [ 287 ], licochalcone A [ 288 ], genipin [ 97 ] and gastrodin [ 289 ] also demonstrate neuroprotective effects by up-regulating NRF2 pathway in different PD models.…”
Section: Potentials Of Antioxidants In Treating Parkinson’s Diseasmentioning
confidence: 99%
“…However, orally administrated trehalose could be greatly digested by intestinal trehalase before entering into the brain, resulting in its pharmacological ineffectiveness [ 21 , 22 , 23 ]. Melibiose (MEL), an analogue of trehalose, might be maintained with a high therapeutic concentration in the brain by oral administration due to absence of intestinal melibiase [ 24 ]. Moreover, a study has indicated that melibiose could cross the blood-brain barrier (BBB) [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the brain, activated microglia release proinflammatory mediators in response to neuroinflammation [ 33 ]. To investigate α-synuclein induced inflammation in mouse BV-2 microglial cells, α-synuclein fibrils prepared from the Escherichia coli -derived α-synuclein [ 34 ] were used to activate BV-2 cells ( Figure 1 a). As shown in Figure 1 b, the resting BV-2 microglia exhibited a ramified morphology.…”
Section: Resultsmentioning
confidence: 99%
“…The A53T mutation is a point mutation of α-synuclein that enhances its rate of fibrillization, leading to early-onset PD [ 73 ]. A53T mutation was introduced into SNCA cDNA [ 34 ] by site-directed mutagenesis (QuikChange II XL mutagenesis kit; Stratagene, La Jolla, CA, USA) using primer 5′-GTGGTGCATGGTGTG A CAACAGTGGCTGAGAAG-3′ (mutated nucleotide underlined) and sequenced. Then the A53T SNCA cDNA acid (and GFP (from pEGFP-N1, Invitrogen) were subcloned into pcDNA5/FRT/TO (Invitrogen) to generate in-frame A53T SNCA-GFP.…”
Section: Methodsmentioning
confidence: 99%